NAQ's 40th Birthday Nursing: Predictions From the Past; Predictions for the Future, Parts I & II. Issue 4 (October 2016) - McClure, Margaret L.; Batcheller, Joyce
Abstract : The following two articles relate to Nursing's past and future, described through a series of predictions made by one of Nursing's great leaders Margaret L. McClure (Maggie McClure). It is reprinted from NAQ Fall 2000, Volume 25, Issue 1. The second article, by another great leader, Joyce Batcheller, DNP, RN, NEA-BC, FAAN, is a follow up on those predictions, reflecting on Nursing today and tommorow.